Simple approaches to measuring and managing Trinidad and Tobago's commercial banks foreign currency exposure - Matthias, Rudy...[et al.] ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 2000)
Measures commercial banks exposure to foreign exchange risk. Suggests a simple approach to managing that exposure to ensure the stability of the domestic financial system.